Gender differences in perceived legitimacy and status perception in leadership role - Cha, Hyunjin; Uchida, Yukiko; Choi, Eunsoo (Frontiers in Psychology, 2023)
The present study examined the difference between women and men in perceiving leadership roles. Two experiments, one conducted online and the other in a lab, investigated the subjective experiences of Japanese men and women when they are assigned with different roles (e.g., leader vs. subordinate). Both studies revealed that women perceived their role as less legitimate when they were assigned leader role (vs. subordinate role). In contrast, men did not differ in their perceived legitimacy according to the assigned roles. This discrepancy in legitimacy perception in response to different roles between men and women accounted for a significant variance in women’s lower sense of status when they were a leader (vs. subordinate), but not among men. Our study results illustrate the psychological barrier operating for women in organizations that are embedded in a cultural context in which women leaders are highly underrepresented.